2014
DOI: 10.1371/journal.pone.0089759
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Subset of Heat Stress Induced Genes of Mycobacterium tuberculosis Is Regulated by 3',5'-Cyclic AMP

Abstract: Mycobacterium tuberculosis (Mtb) secretes excess of a second messenger molecule, 3',5'-cyclic AMP (cAMP), which plays a critical role in the survival of Mtb in host macrophages. Although Mtb produces cAMP in abundance, its exact role in the physiology of mycobacteria is elusive. In this study we have analyzed the expression of 16 adenylate cyclases (ACs) and kinetics of intracellular cAMP levels in Mtb during in vitro growth under the regular culture conditions, and after exposure to different stress agents. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Our results suggest that hsp60-driven Rv2212 induces a phenotype resembling stressed mycobacteria, where gene regulation of chaperones might induce the capacity of adaptation to macrophage infection, mediated by proteins related with correct folding and metabolic pathways. In agreement with this proposal, it has just been shown that dnaK, grpE, dnaJ, and Rv2025c are regulated by cAMP in M. tuberculosis (Choudhary et al 2014). We acknowledge that other proteins we found differentially expressed in response to Rv2212 in BCG have not previously been shown to respond directly to CRP, therefore indicating either cAMP produced by Rv2212 activity might be modifying primary targets to then affect BfrB, GroEL2, BCG0191, and PepA, or that these proteins respond to general stress.…”
Section: Discussionsupporting
confidence: 67%
“…Our results suggest that hsp60-driven Rv2212 induces a phenotype resembling stressed mycobacteria, where gene regulation of chaperones might induce the capacity of adaptation to macrophage infection, mediated by proteins related with correct folding and metabolic pathways. In agreement with this proposal, it has just been shown that dnaK, grpE, dnaJ, and Rv2025c are regulated by cAMP in M. tuberculosis (Choudhary et al 2014). We acknowledge that other proteins we found differentially expressed in response to Rv2212 in BCG have not previously been shown to respond directly to CRP, therefore indicating either cAMP produced by Rv2212 activity might be modifying primary targets to then affect BfrB, GroEL2, BCG0191, and PepA, or that these proteins respond to general stress.…”
Section: Discussionsupporting
confidence: 67%
“…rpoB encodes for DNA-dependent RNA polymerase, and mutations within rpoB can result in rifampicin resistance (44,45). dnaK encodes heat shock protein that is the most abundant protein within Mtb and plays a crucial role in preventing partially misfolded proteins from aggregating by binding to hydrophobic residues, which then allows these proteins to refold (46). As such, coordinated transcriptional and proteomic regulation of these known and proposed Clp protease substrates is crucial to the transition from a metabolically active to dormant state.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was demonstrated in M. tuberculosis that increased cellular levels of cAMP by heat stress or exogenous dibutyryl cAMP treatment led to upregulation of some heat stress-induced genes that have the Crp-binding sequences in their control regions, strongly indicating that the cellular cAMP level correlates with expression levels of the Crp regulon [66]. In this study, we observed both reduced expression of ahpC in a PDE-overexpressed strain of M. smegmatis relative to the control strain and an increase in cellular levels of cAMP under oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%